Analysis of the fiscal burden in Bosnia and Herzegovina and the European Union - Rovčanin, Adnan (Naše gospodarstvo, 2010)
This paper analyses the importance of the fiscal burden for the national economy and the relationship between taxes and gross domestic product. This paper examines tax participation - the most important part of state treasury - in the gross domestic product (GDP) as well as the fiscal burden in B&H and the European Union (EU) countries from the aspect of direct and indirect taxes. Finally, the significance of relationship between the GDP and Value Added Tax (VAT) is analysed. The example of EU 27 and B&H demonstrates the intensity of the impact and relationship of stated values in a certain time period in addition to mutual comparisons.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; European Union; Evropska unija; davčna politika; davki; tax; bruto domači proizvod; ekonomska analiza